Enhancing the strength, ductility and strain hardening of B2-strengthened refractory multi-principal-element alloys by suppressing dislocation glide channels - Jingyu Pang; Yitong Yang; Chunjin Chen; Long Zhang; Aimin Wang; Shijian Zheng; Qing Wang; Hongwei Zhang (Materials Research Letters)
Refractory multi-principal-element alloys (RMPEAs) typically exhibit low strain hardening capacity and may even experience strain softening, which poses a risk to the structural integrity of materials. We first established that the strain softening observed in Ti1.5Al0.5ZrNb RMPEA is due to the planar slip of dislocations and the formation of narrow <111>{110} orientation dislocation channels (DCs). Subsequently, we introduced nanoscale ω-AlZr2 precipitates that are diffusely distributed around grain boundaries (GBs), which significantly enhance the strength and strain hardening capacity of the RMPEA by inhibiting the formation of narrow DCs. This approach is highly versatile and can effectively improve deformation stability.